Curriculum Coherence in Higher Education: Some Reflections - González García, Victoria (2018)
In the framework of the research entitled Relating pedagogy, curriculum and didactics: the case of the majors offered by the University of Costa Rica, reaccredited by SINAES, this essay shares some theoretical reflections from a Iberoamerican perspective, enriched with the contributions of people interviewed, who coordinate or lead projects and programs directly linked to the teaching faculty of the University of Costa Rica with the purpose of promoting the improvement of teaching performance. The essay is structured in two parts: the first part is a reflection on education, pedagogy, curriculum and didactics in order to understand the pedagogical bases of the majors under study. In the second part, these concepts are reviewed in the light of three pedagogical approaches with the idea of promoting that faculty members identify themselves with one of these approaches according to their teaching interests and practical application.